PREFERENSI ORANG TUA DAN SANTRI DI BREBES TERHADAP PENDIDIKAN PESANTREN PASCASEKOLAH DASAR - Fina Nur Hidayati; Didi Pramono (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2026)
This study aims to analyze the preferences of parents, students, and the integration of James S. Coleman's rational choice theory in Siwuluh Village, Bulakamba District, Brebes Regency, Central Java, regarding the choice of post-primary Islamic boarding school education. This study is qualitative and uses a case study technique. Data collection uses interview, observation, and documentation techniques. Informants consist of 11 participants consisting of 6 main informants (MFZ, KU, SY, LF, SIM, and WFR), 4 supporting informants (N, R, T, and LNA), and 1 key informant (RA) who has experience in Islamic boarding school education. The data validity technique in this study uses source triangulation. Data are analyzed qualitatively using the approach proposed by Miles, Huberman, and Saldana in the form of data condensation, data models (data display), and making and validating conclusions. The results show that parents and students assess education in Islamic boarding schools positively. Parents' and students' preferences are influenced by family, social, environmental, religious, and reputational factors, as well as comparisons with other similar educational institutions, and are the result of rational considerations. The decision to send children to post-primary school is a rational one based on a cost-benefit analysis. Benefits such as instilling religious values, developing good character and morals, strict social supervision, and protection from negative influences far outweigh the relatively low economic costs.